Arthroscopic Rotator Cuff Repair With Muscle Advancement and Artificial Biodegradable Sheet Reinforcement for Massive Rotator Cuff Tears. Issue 10 (30th October 2020) - Yokoya, Shin; Harada, Yohei; Negi, Hiroshi; Matsushita, Ryosuke; Matsubara, Norimasa; Adachi, Nobuo
Background: Because high failure rates have frequently been reported after arthroscopic rotator cuff repair (ARCR) of massive rotator cuff tears (mRCTs), we introduced the technique of ARCR with supraspinatus and infraspinatus muscle advancement (MA). However, for cases where the original footprint cannot be completely covered, additional surgery using an approved artificial biomaterial is performed. Purpose: To investigate the postoperative clinical outcomes and failure rate after MA-ARCR, with and without our reinforcement technique. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 74 patients (mean ± SD age, 68.7 ± 7.7 years) diagnosed with mRCT with a minimum postoperative follow-up of 2 years were included in the current study. Of these patients, 47 underwent MA-ARCR with polyglycolic acid (PGA) sheet reinforcement (study group), and 27 patients underwent MA-ARCR alone (control group). PGA reinforcement was performed when full coverage of the footprint could not be achieved by MA alone, but where the latter was possible, reinforcement was not required. Thus, the study group had significantly worse muscle quality than the control group ( P < .05). The pre- and postoperative range of motion (ROM), isometric muscle strength, acromiohumeral interval, and clinical outcomes were evaluated and compared between these 2 groups. Cuff integrity during the last follow-up period was assessed with magnetic resonance imaging, and the failure rate was calculated. In addition, the postoperative foreign body reaction was investigated in the study group. Results: In both groups, significant postoperative improvements were seen in acromiohumeral interval, clinical scores, ROM in anterior flexion, and isometric muscle strength in abduction, external rotation, and internal rotation ( P < .001 for all). The failure rate of the study group was 12.8% (6 patients) and that of the control group was 25.9% (7 patients). No significant differences were noted between the 2 groups on any of the data findings, even regarding the failure rate. Foreign body reactions in the early period were found in 3 patients, although these spontaneously disappeared within 3 months. Conclusion: Patients who underwent PGA patch reinforcement for MA-ARCR when the footprint could not be completely covered had clinical results similar to isolated MA-ARCR when the footprint could be covered. Both procedures resulted in significant improvement in symptoms and function compared with preoperatively.